Jebel Kareem (TH.68): Techno‐typological characteristics of a distinctive lithic assemblage from Dhofar, southern Oman. (26th November 2019) - Hilbert, Yamandú H.
Abstract : The lithic sample from TH.68 in Southern Oman is characterised by a set of techno‐typological features: (a) the variety of blank production strategies employed to produce flakes, blades and bladelets; (b) the level of standardisation of tools, including backed bladelets, end scrapers, burins on truncation, unifacial and bifacial plano‐convex points, etc.; and (c) a previously unknown technique that produced specific flakes presenting uniform morphological traits and high incidence of retouch. Here a comprehensive account of the lithic production systems employed by prehistoric human bands and the formal retouched tools that they made is provided.